Characterization of Subtilin L-Q11, a Novel Class I Bacteriocin Synthesized by Bacillus subtilis L-Q11 Isolated From Orchard Soil - Qin, Yuxuan; Wang, Yao; He, Yinghao; Zhang, Ying; She, Qianxuan; Chai, Yunrong; Li, Pinglan; Shang, Qingmao (Frontiers in Microbiology, 2019)
Bacteriocins are peptides or proteins synthesized by bacterial ribosomes that show killing or inhibitory activities against different groups of bacteria. Bacteriocins are considered potential alternatives to traditional antibiotics and preservatives in pharmaceutical and food industries. A strain L-Q11 isolated from orchard soil was phylogenetically characterized as Bacillus subtillis based on 16S rRNA gene sequencing analysis. A novel class I bacteriocin (Subtilin L-Q11), was identified and purified from L-Q11 cell-free supernatant in a four-step procedure, including salt precipitation, cation exchange, gel filtration and reverse-phase high-performance liquid chromatography (RP-HPLC). The molecular mass (3,552.894 Da) of this novel bacteriocin was determined by Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The purified Subtilin L-Q11 exhibited optimal features in pH tolerance, thermostability, and sensitivity to proteases. Further, Subtilin L-Q11 showed inhibitory activities against a number of bacteria including some human pathogens and food spoilage bacteria, in particular Staphylococcus aureus. All these important features make this novel bacteriocin a potential candidate for development of new antibacterial drug or food preservative in the future.